Repeated sprint ability in soccer players: associations with physiological and neuromuscular factors - Baldi, M.; Da Silva, J. F.; Buzzachera, C. F.; Castagna, C.; Guglielmo, L. G. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The aim of this study was to examine the relationship between repeated sprint ability (RSA, 6×40 m [20+20 m] with 20-s recovery) and neuromuscular and aerobic fitness variables in male collegiate soccer players.